Analysis on the Selection of Prefabricated Box-Shaped Steel Grid-Concrete Composite Thin-Shell Roof Structure. Issue 2 (April 2021) - Hong, Cheng; Yu, Jiaxing; Zhang, Baohua; Liu, Kai; Ming, Xia
Abstract: The new fabricated box-shaped steel grid-concrete composite thin-shell roof structure is a new structure based on the large-span steel-concrete composite thin-shell roof. An assembly unit composed of thin-walled steel ribs with bolt holes, a steel bottom plate, and concrete, and a thin-shell roof structure formed by assembly connection between the assembly units. A comparative analysis of the deformation and stress of the flat roof and arched roof structure shows that when the span is less than 30m, the difference between the deformation and stress of the two structures is not large, and it is more reasonable to choose the flat assembled composite roof structure. The construction difficulty is lower. When the span is 40m, the maximum vertical displacement of flat roof and arched roof are 53.73mm and 17.81mm respectively, and the difference gradually increases from 40m. After the span exceeds 40m, the stress between the steel box and concrete of the flat roof structure. The ratio increases sharply, and the arched roof shows a uniform change trend. The material utilization rate of the arched roof is higher than that of the flat roof.